G307(P) National trainees service evaluation of the management of idiopathic intracranial hypertension (iih) – pseudotumor cerebri in children. (12th March 2018) - Amin, A; Spaull, R; Rattihalli, R; Atherton, M; Mundada, V; Pilley, E; Moran, M; Markham, L
Abstract : Introduction: IIH is characterised by raised intracranial pressure mostly affecting young females. It can lead to severe and irreversible visual loss. There is little consensus or evidence based guidance for management, especially in children. We conducted a multi-centre retrospective service evaluation to better understand current practice. Methods: Children diagnosed with IIH from nine centres in the UK over a 3 year period were retrospectively studied. Patient demographics, clinical details at presentation and follow-up, comorbidities, investigations, and medications were recorded and analysed. Results: 105 patients (71 females) with IIH, median age 11 [IQR 5–13] were recruited. Overall, record keeping was suboptimal with no recorded weight in 33% (43/105), height in 64% (68/105); and visual acuity in 24% (26/105). At presentation 42/62 (67%) of the patients had weight >90 th centile, behavioural issues were reported in 15/63 (23%) and missing school in 9/43 (20%). Papilloedema was reported in 98/105 (93%) at baseline and in 87/105 (82%) at 6 months. Median GA opening CSF pressure was 34 (IQR 28 to 40) cm H2O and non-GA was 32 (IQR 25 to 39). 1/105 (0.9%) had ICP monitoring and 1/105 (1%) had shunt. 73 (69%) were seen by an ophthalmologist and 48 (45%) had no record of either orbital US scan or OCT. Only 16 (15%) had MRV and/or MRA. 51 (48%) had LP under GA, of whom only 10 (19.6%) had CO2 monitoring recorded. 92/105 (87%) received acetazolamide, however 25/92 (27%) had no electrolytes checked during acetazolamide therapy. Conclusions: This project highlights significant variation in the way that IIH is being investigated and managed in the UK. This variation is likely to reflect the paucity of evidence, but risks over-diagnosis and inappropriate management. These results should be used to form the basis for a national consensus for the diagnosis and management of IIH in young people.